Earthquake alarm detector / Nik Aqil Farihin Nik Mohd Azizee - Nik Mohd Azizee, Nik Aqil Farihin (2024)
An earthquake is an inherently unpredictable natural occurrence that is impossible to prevent but can be forecasted. Constructing reliable early warning systems is crucial since earthquakes pose a significant threat to both infrastructure and human life. An earthquake alarm detector is crucial in Malaysian contexts due to the nation's location in a seismically active area of Southeast Asia. The primary objective of this study is to create and implement a comprehensive early warning system that is specifically tailored to the distinct seismic characteristics of Malaysia. The proposed Earthquake Alarm Detector would utilize advanced seismic sensors, real-time data processing algorithms, and communication technologies to deliver prompt and accurate warnings, therefore mitigating the impact of earthquakes. This methodology utilizes information regarding the geological attributes of Malaysia, taking into consideration the likely sources and magnitudes of seismic events in the region. The Earthquake Alarm Detector comprises a network of seismic sensors strategically positioned to monitor high-risk regions, a central processing unit for instantaneous data analysis, and a communication interface for prompt notification of relevant authorities and the public. The Earthquake Alarm Detector has the potential to revolutionize catastrophe prevention and response strategies in Malaysia. The primary objective of the system is to safeguard critical infrastructure, minimize casualties, and enhance the ability of the community to withstand seismic hazards through the issuance of timely warnings. Besides, this project's objective is also to decrease reaction times, since this facilitates the process of evacuation and emergency preparedness. This project contributes to the expanding field of earthquake early warning systems by providing an appropriate solution for a specific location with distinct geological characteristics. The ADXL335 accelerometer sensor detects pre-earthquake tremors. The accelerometer detects vibrations and converts them into corresponding ADC data. Subsequently, the Arduino microcontroller processes the aforementioned digital data. Subsequently, Arduino evaluates these numbers about the predetermined threshold value. If the sample value exceeds the threshold value, Arduino will activate an LED, activate the buzzer, and display a message on the 16x2 LCD regarding the status of the alarm. A call alert is initiated to the registered mobile phone using the GSM module. Whenever a violation is detected, the registered mobile phones receive a call alert.